O procesach zmian w kulturach rdzennych ludów syberyjskich po upadku Związku Radzieckiego. Przypadek kultury buriackiej = On the processes of change in the cultures of the indigenous peoples of Siberia after the fall of the soviet union. The case of Buryat culture - Połeć, Wojciech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to analyse the selected changes within the cultures of indigenous peoples in Siberia after the dissolution of the Soviet Union, or more precisely after the political and social transformations that took place after the "fall of communism" as exempli?ed by the Buryat culture. An analysis of the theoretical concept of "policy of cultural revival", which is widespread in the literature on the subject, is followed by the analysis of the connection between the revival of the cultures of Siberian indigenous peoples and the religious revival in Siberia.
Keywords: Syberia (Rosja); Buriaci; polityka odrodzenia kultur; odrodzenie religijne; Związek Radziecki; Siberia; Buryats; policy of cultural revival; religious revival; Soviet Union